Efficient Delivery and Nuclear Uptake Is Not Sufficient to Detect Gene Editing in CD34+ Cells Directed by a Ribonucleoprotein Complex - Shirin R. Modarai; Dula Man; Pawel Bialk; Natalia Rivera-Torres; Kevin Bloh; Eric B. Kmiec (Elsevier, 2018)
CD34+ cells are prime targets for therapeutic strategies for gene editing, because modified progenitor cells have the capacity to differentiate through an erythropoietic lineage. Although experimental advances have been reported, the associated experimental protocols have largely been less than clear or robust. As such, we evaluated the relationships among cellular delivery; nuclear uptake, often viewed as the benchmark metric of successful gene editing; and single base repair. We took a combinatorial approach using single-stranded oligonucleotide and a CRISPR/Cas9 ribonucleoprotein to convert wild-type HBB into the sickle cell genotype by evaluating conditions for two common delivery strategies of gene editing tools into CD34+ cells. Confocal microscopy data show that the CRISPR/Cas9 ribonucleoprotein tends to accumulate at the outer membrane of the CD34+ cell nucleus when the Neon Transfection System is employed, while the ribonucleoproteins do pass into the cell nucleus when nucleofection is used. Despite the high efficiency of cellular transformation, and the traditional view of success in efficient nuclear uptake, neither delivery methodology enabled gene editing activity. Our results indicate that more stringent criteria must be established to facilitate the clinical translation and scientific robustness of gene editing for sickle cell disease.